Analysis of students' mental models using the flipped classroom learning model - Hasibuan, Nur Azizah Putri; Hilda, Lelya; Hsb, Rafikah Rezky (J-PEK (Jurnal Pembelajaran Kimia), 2024)
This research analyses the flipped classroom learning model on students' mental model on salt hydrolysis material. This research was conducted at SMAN 1 Ulu Barumun, Padang Lawas Regency. The research subjects were 11th-grade science students, totalling 20 students. The study used a two-tier test instrument, student observation, and in-depth interviews. The results showed that most students achieved the scientific mental model (38.33%), which reflects deep understanding and the ability to connect concepts with phenomena scientifically. In addition, 31.52% of students were at the synthesis mental model, where they began to understand the concept, but there were still misconceptions. Meanwhile, 30.13% of students were in the initial mental model, with limited and inaccurate understanding. Factors such as teacher explanation, learning experience, and learning resources used play an important role in achieving the scientific mental model. Overall, flipped classrooms are proven to be an effective learning strategy and are worth applying to improve the quality of learning and form students' mental models on salt hydrolysis material.